2013
DOI: 10.12968/live.2013.18.5.150
|View full text |Cite
|
Sign up to set email alerts
|

Uterine disease in dairy cattle: monitoring and management

Abstract: Uterine disease is a common cause of infertility and thus economic loss in dairy herds, yet in many herds the true incidence of disease is unknown. Accurate monitoring, identification and recording are essential to highlight when the incidence of uterine disease is too high and intervention is required. While prevention is always preferable to cure, when cases of uterine disease do occur it is important that they are treated and managed correctly to reduce any further impact on subsequent performance. This cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Post-partum uterine health is a critical factor when considering the fertility of dairy cows and the consequent duration of the CCI (1214). Many studies have demonstrated the negative impact of endometritis on the reproductive performance of dairy cows and subsequent increased CCI (1517).…”
Section: Introductionmentioning
confidence: 99%
“…Post-partum uterine health is a critical factor when considering the fertility of dairy cows and the consequent duration of the CCI (1214). Many studies have demonstrated the negative impact of endometritis on the reproductive performance of dairy cows and subsequent increased CCI (1517).…”
Section: Introductionmentioning
confidence: 99%